Characteristics Of Preparing The Army For Combat Operations In The Time Of Amir Temur - Dustov, Asrorbek Gadoyevich (TLEP – International Journal of Multidiscipline, 2025)
This article analyzes the specific characteristics of preparing military forces for combat operations during the reign of Amir Timur in the 14th-15th centuries. According to the research findings, the military training system of Timur’s era was among the most advanced and effective systems of its time, ensuring not only physical preparation but also strategic thinking, tactical mastery, and high discipline.